Analisis Faktor yang Mempengaruhi Employee Engagement pada Rumah Sakit Umum Pusat Prof. Dr. I.G.N.G Ngoerah - Merta I Ketut; Agus Suwarna Putra I Kadek; Yusnimi Ni Made (Journal on Education, 2024)
The objectives of this research are: Analyzing Employee engagement open and honest communication, Employee engagement Leadership, Employee engagement job design, Employee engagement Learning among employees at Prof. Central General Hospital. Dr. I.G.N.G Ngoerah. This type of research is associative, aims to determine the influence of the independent variable on the dependent variable and how close the influence or relationship is and to determine whether there is a correlation between the two variables. The researcher used the Slovin formula to determine the sample because the population was more than 100 respondents in the sample calculation with an error rate of 10%. The data analysis techniques used in this research to analyze the data are: (1) Quantitative Analysis, (2) Validity Test, (3) Reliability Test, (4) Path Analysis assisted by data processing with SPSS version 24. Research This results in the influence of the variables Leadership, Open and Honest Communication, and Learning Technology on Employee Engagement of Employees at Prof. Ngoer's central hospital which is quite moderate and shows that Learning Technology can mediate smooth Employee Engagement of Employees.